56.6k views
0 votes
3+6x=2x+27. how to solve


2 Answers

2 votes

Answer:

x = 6

Explanation:

To solve for x, we have to isolate the x. Our first step is to subtract 2x from both sides:

3+6x=2x+27

3+4x=27

Then, we subtract 3 from both sides of the equation so the 4x term is alone on the left side of the equation:

3+4x=27

4x=24

Finally, we divide both sides of the equation by 4 so x is all alone:

4x=24

x=6

User Yannan Wang
by
5.9k points
0 votes

9514 1404 393

Answer:

x = 6

Explanation:

You want x on one side of the equation and a constant on the other side. Subtract the terms you don't want where they are.

Here, the smaller x-term is on the right, so we can subtract that to put all the x-terms on the left. The left side has a constant of 3 that we will not want there with the x-terms. So, we can subtract 2x+3 from both sides to get ...

3 +6x -(2x +3) = 2x +27 -(2x +3)

4x = 24 . . . . . . simplify

x = 24/4 . . . . divide by the coefficient of x

x = 6

User AnthoPak
by
5.2k points